Feasibility of Using Green Tea Powder as a Natural Antioxidant and Stevia as a Sweetener in Non-Fermented Layer Cake - Leila Nateghi; Fatemeh Zarei (Journal of Nutrition and Food Security, 2023)
Today there is an increasing demand for low-calorie and functional food products worldwide. Green tea powder (GTP) has antioxidant property due to its phenolic structure which makes it a good natural replacement for synthetic antioxidants. Stevia is a calorie-free product which can be substituted for sucrose in foods. The aim of this study was to investigate the feasibility of using GTP and stevia instead of flour and sugar, respectively, in the formulation of non-fermented layer cake. Methods: To do so, different concentrations of GTP (10, 20, 30% w/w) and stevia (40, 60, 80% w/w) were incorporated into the formulation of cake. Ten treatments were designed and the rheological properties of dough including farinograph and extensograph characteristics were measured. Three dough samples with superior rheological properties along with control sample were baked. The physicochemical and sensory properties of the selected samples were compared with those of control sample. Results: The layer cakes containing 10% GTP and 40%, 60%, and 80% stevia were selected as the superior treatments and their quality properties were compared with those of control sample. Increased concentration of stevia significantly reduced the specific volume and increased the firmness of the layer cake samples. There was no significant difference in total acceptance between the layer cakes containing GTP and stevia and control sample. Conclusion: The treatment containing 10% green tea powder and 80% stevia was selected as the superior treatment regarding the nutritional and quality properties.